Agreement Between Emergency Department Admission and Hospital Discharge Diagnoses; A Retrospective Observational Study - Arif Ishtiq Mattoo; Saad Al-shahrani; Farhat Anjum Mattoo; Saad Al-Asiri; Amjad Obeid; Donnie Neil Sarmiento; Qasem Ahmed Almulihi; Abdullah Saad Al-shahrani (Archives of Academic Emergency Medicine)
Introduction: An accurate emergency department (ED) diagnosis is critically important for providing proper treatment during the so-called “Golden Hour.” This study aimed to evaluate the agreement between admitting and discharge diagnoses in ED.